ANALISIS KEBIJAKAN PENDIDIKAN PEMERINTAH KOLONIAL DAN IMPLIKASINYA TERHADAP PENDIDIKAN ISLAM - Marisa Hannum Harahap (CV. Adiba Aisha Amira, 2023)
The arrival of the Dutch as colonialists to the Indonesian archipelago brought many changes to all existing systems, especially for Muslim communities that once existed in strong Muslim kingdoms. When the archipelago was controlled by colonial invaders, many of the policies implemented both from a political, social and economic perspective were quite different from before. At that time, these policies had an impact on the educational policies that were later regulated by the Netherlands, including the teachers, the material delivered, the facilities and infrastructure that supported the learning process and so on. Even policies on the establishment of religious schools are regulated, all of which are expected not to interfere with the rules set by the Netherlands. So, analyzing the policies issued by the Dutch government during their colonization in Indonesia, it turns out that many of them were detrimental to the Islamic ummah. For example, many graduates from religious schools were not accepted, then religious teachers were marginalized and even their materials had to get permission from the Dutch government, every learning process was always monitored because there was fear of rebellion. This makes Islamic education less flexible and difficult to develop. However, efforts to continue to fight for and maintain Islamic education are continuously realized by establishing several educational institutions such as Islamic boarding schools and madrasas. The materials at the Madrasah were doubled with religious and general learning, so that students could be accepted among the Dutch government at that time.